Analisis Keputusan Konsumen Dalam Membeli Minyak Goreng Di Kabupaten Nganjuk - Bhirawa, Sigit Wisnu Setya; Larasati, Dyah Siti Ayu; Putri, Elvika Nungki Chintia; Kusuma, Bela; Anitasari, Silvia; Meilina, Restin (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: This research analyzed the variables that influence the buying decision of cooking oil in Nganjuk Regency. Methods: The method used is quantitative analysis. Research Finding: The study's results show that the only variables significantly affecting purchasing decisions are price and personal factors, while product, promotion, and social factors do not. Personal factors, including age, occupation, economic situation, lifestyle, and personality, have the most dominant influence on the decision to buy cooking oil in Nganjuk Regency. Theoretical contribution/Originality: This study's results strengthen the consumer behavior theory by providing examples of how it is implemented in buying cooking oil in Nganjuk Regency. Practitioner implication: It can be the basis for policy-making to shift people's purchasing interest from bulk cooking oil to packaged cooking oil and can be the basis for determining cooking oil marketing strategies according to consumer behavior. Research limitation: Analysis of factors that influence buying decisions for cooking oil in the Nganjuk district in this study is limited to only product variables, price, promotion, personal factors, and social factors